2017
DOI: 10.1055/s-0043-109239
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Hoodia, Chamomile, Terminalia Species and Evaluation of Commercial Preparations Using Ultrahigh-Performance Liquid Chromatography Quadrupole-Time-of-Flight Mass Spectrometry

Abstract: Ultrahigh-performance liquid chromatography quadrupole-time-of-flight mass spectrometry (UHPLC-QToF-MS) profiling was used for the identification of marker compounds and generation of metabolic patterns that could be interrogated using chemometric modeling software. UHPLC-QToF-MS was used to generate comprehensive fingerprints of three botanicals (, and chamomile), each having different classes of compounds. Detection of a broad range of ions was carried out in full scan mode in both positive and negative mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Identified compounds from Terminalia catappa nut and Terminalia subspathulata fruit extracts using UHPLC-ESI-MS/MS Values based on total ion chromatogram (TIC) of Terminalia catappa for compounds common to both extracts detected only in the nuts of T. catappa but not in the fruits of T. subspathulata. It has been previously reported in the fruits of T. chebula(Avula et al, 2017).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Identified compounds from Terminalia catappa nut and Terminalia subspathulata fruit extracts using UHPLC-ESI-MS/MS Values based on total ion chromatogram (TIC) of Terminalia catappa for compounds common to both extracts detected only in the nuts of T. catappa but not in the fruits of T. subspathulata. It has been previously reported in the fruits of T. chebula(Avula et al, 2017).…”
mentioning
confidence: 72%
“…Oyeleye et al (2018) has previously reported the presence of gallic acid in the leaf and stembark of T. catappa. Compound 3, with [M-H]at m/z 331, was identified as glucogallin, a monogalloylglucose, based on tandem mass at m/z 211 and 169 for sequential loss of the glucose moiety, 162 amu (Avula et al, 2017;Kumar et al, 2015). Compounds 14 and 21, with [M-H]at m/z 483 and m/z 635, were identified as digalloylglucose and trigalloylglucose, respectively, based on the tandem mass arising from losses of the corresponding number of galloyl moieties (Singh et al, 2016).…”
Section: Gcms Metabolite Profile Of Hexane Fractionsmentioning
confidence: 99%
“…As such, metabolomics provides a powerful tool for understanding the complete chemical makeup of an herbal product, which can be used for efficient and accurate quality control and authentication. Metabolomics characterizes the chemical relationships that underlie variations based upon genotype, origin (50), climate (51), or other biotic or abiotic interactions (52)(53)(54). While a variety of analytical inputs can be used to generate metabolome data -including Fourier-Transformed infrared spectroscopy (FT-IR), charged aerosol detection (CAD), ultraviolet-visible (UV/VIS) spectrophotometry, mass spectrometry (MS), and Nuclear Magnetic Resonance (NMR) spectroscopy -the two primary analytical approaches employed for the majority of metabolomics studies are liquid chromatography coupled to mass spectrometry (LC-MS) and NMR spectroscopy.…”
Section: Metabolomicsmentioning
confidence: 99%
“…0.5 mL of supernatant was used for UHPLC-MS analysis after a subsequent spin at 5000 g at 10 ºC for 20 minutes and transferring 250 µL of the sample into glass autosampler vials with inserts. For GC-MS (Gas Chromatography-Mass Spectrometry) analyses of primary polar metabolites, 0.5 mL water was added the remaining extract used above for the UHPLC preparation, sonicated for 5 min, extracted for 30min, and centrifuged at 3000 g. 0.5 mL of the polar extract was subsequently dried under nitrogen and derivatized using previously established protocols (35). Briefly, N-Methyl-N-(trimethylsilyl) trifluoroacetamide (MSTFA) with 1 % TMCS (2,2,2-Trifluoro-Nmethyl-N-(trimethylsilyl)-acetamide, Chlorotrimethylsilane) was used to derivatize the polar metabolites, after treatment with methoxyamine-HCl-pyridine.…”
Section: Ultra-high Performance Liquid Chromatography and Mass Spectrmentioning
confidence: 99%